Revision of the flightless click-beetle genus Dima Charpentier, 1825 (Coleoptera: Elateridae: Dimini) in the Balkan Peninsula - Mertlik, Josef; Németh, Tamás; Kundrata, Robin (Zootaxa, 2017)
The genus Dima Charpentier, 1825 in the Balkan Peninsula and surrounding areas was revised based on the adult semaphoronts. Altogether 33 species are known from the investigated area, of which nine are new for science: D. bruhai sp. nov. (Greece), D. dusaneki sp. nov. (Macedonia), D. fialai sp. nov. (Macedonia), D. kozufensis sp. nov. (Greece, Macedonia), D. orientalis sp. nov. (Bulgaria), D. pelikani sp. nov. (Albania, Montenegro), D. pelionensis sp. nov. (Greece), D. vonickai sp. nov. (Albania), and D. zbuzeki sp. nov. (Greece). Dima peloponnensis Schimmel & Platia, 2008 was synonymized under D. assingi Schimmel & Platia, 2008, D. scutellaris Platia, 2010 and D. fokidensis Schimmel & Platia, 2008 were synonymized under D. fthiotidensis Schimmel & Platia, 2008, D. pindosensis Schimmel & Platia, 2008 was synonymized under D. raineri Wurst, 1997, and D. riesei Platia, 2010 was synonymized under D. vailatii Schimmel & Platia, 2008. For the first time, a male was described for D. florinensis Platia, 2012, and females for D. neumanni Platia, 2013, D. olympica Meschnigg, 1934, and D. schimmeli Platia & Gudenzi, 2009. Dima dalmatina Küster, 1844 was recorded for the first time from Bosnia and Herzegovina, D. elateroides Charpentier, 1825 from Bulgaria and Macedonia, D. florinensis from Macedonia, and D. raineri Wurst, 1997 from Albania. For each species we provided bibliography and information on the type depositories, diagnosis, intraspecific variability and distribution, and figured the main diagnostic morphological characters. Due to the generally uniform morphology within the genus and great intraspecific variability in most diagnostic characters we were unable to construct a reliable identification key for the Dima species in the Balkan Peninsula. Our study revealed that Dima is a more speciose genus than expected and that more species may be discovered in the near future, even in Europe.